Family study of sensation seeking - Bratko, Denis (Array, 2003)
The paper presents the results of the family study of sensation seeking. The sample consisted of high school students and their parents: 151 offspring (95 females and 56 males), 148 mothers and 118 fathers. Both offspring and their parents completed Sensation Seeking Scale - Form V (SSS-V). Parents also completed the Parental Behaviour Scale (PBS). Parental Behaviour Scale is a measure of parental behaviour developed for the purpose of this research. It consists of 10 items measuring two dimensions of parental behaviour: parental affection and parental control. Each parent had to report his/her own behaviour, as well as the behaviour of their partners. Parents' SSS-V and PBS scores were related with the offsprings' SSS-V scores. Father-offspring correlations ranged between 0.18 and 0.27 for different sensation-seeking subscales, while mother-offspring correlations ranged between 0.02 and 0.24. Regressions of offspring on midparent scores ranged between 0.19 and 0.32. Mother-father correlations were statistically significant for all subscales, except for Thrill and Adventure Seeking Scale, and ranged between 0.26 and 0.46 suggesting assortative mating for sensation seeking in this sample. The only measure from PBS that correlated with children's sensation seeking was fathers' parental control (average fathers' control correlated 0.24 with total children's SSS score).